Combinatorial efficacy of Trichoderma spp. and Pseudomonas fluorescens to enhance suppression of cell wall degrading enzymes produced by Fusarium wilt of Arachis hypogaea.L (International Journal of Agricultural Research, Innovation and Technology, 2018)
Fusarium oxysporum, the soil borne pathogen causes vascular wilt, on majority of crop plants. It has been demonstrated that two different species of Trichoderma and Pseudomonas fluorescens suppress disease by different mechanisms. Therefore, application of a mixture of these biocontrol agents, and thus of several suppressive mechanisms, may represent a viable control strategy. A necessity for biocontrol by combinations of biocontrol agents can be the compatibility of the co-inoculated micro-organisms. Hence, compatibility between Trichoderma spp. and Pseudomonas fluorescens that have the ability to suppress Fusarium oxysporum in vitro on the activity of pectinolytic enzymes of Fusarium oxysporum. The activity of pectinolytic enzymes, i.e. pectin methyl esterase, endo and exo polymethylgalacturonases and exo and endo pectin trans eliminases produced by Fusarium oxysporum (Control) was higher. Maximum inhibition of pectin methylesterase, exo and endo polymethylgalacturonase and exo and endopectin trans eliminase was shown by culture filtrate of Trichoderma viride + Pseudomonas fluorescens (Tv+Pf) (1+2%), followed by Trichoderma harzianum + Pseudomonas fluorescens, (Th +Pf) (1.5+2%) and Trichoderma viride + Trichoderma harzianum (Tv+Th) (1+1.5%). However, pathogenecity suppression of Fusarium oxysporum, a causative of Arachis hypogaea. L by the compatible combination of Trichodema viride + Pseudomonas fluorescens (1+2%) was significantly better as compared to the single bio-agent. This indicates that specific interactions between biocontrol agents influence suppression of pathogenicity factors directly by combinations of these compatible bio-agents.Int. J. Agril. Res. Innov. & Tech. 7 (2): 36-42, December, 2017